NiCoMoMnM-LDH high-entropy material and preparation and application thereof

Synthesis of NiCoMoMnM-LDH high entropy material through hydrothermal reaction and etching method of metal organic frame material templates, solving the problems of poor high temperature resistance and composition differences in the preparation of high entropy hydroxide materials, and achieving high efficiency synthesis and excellent electrochemistry Performance, suitable for supercapacitor positive electrode.

CN119160949APending Publication Date: 2024-12-20NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311366367.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing high entropy hydroxide materials have poor high temperature resistance and different components during the preparation process, resulting in poor cycle stability, making it difficult to apply to supercapacitor electrode materials.

Method used

Using metal organic frame (MOF) material as template, NiCoMoMnM-LDH high entropy material was synthesized by hydrothermal reaction and etching method, combined with density functional (DFT) calculation and analysis of its energy band structure and charge density, and adjusting components to improve the material conductivity.

Benefits of technology

The phase separation and element aggregation of high-entropy materials were successfully avoided, and the efficient and large-scale synthesis of high-entropy hydroxides was achieved, and the specific capacitance and cyclic stability of the material were improved. It was suitable for the positive electrode of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160949A_ABST
    Figure CN119160949A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of supercapacitor electrode materials, and discloses a NiCoMoMnM-LDH high-entropy material and preparation and application thereof.The preparation method comprises the steps that a nickel salt, a cobalt salt, a manganese salt, an M salt and an ethanol water solution form a solution A; forming a solution B from molybdate, 2, 5-dihydroxy terephthalic acid and an organic solvent; mixing the solution A and the solution B, and performing hydrothermal reaction to obtain a precursor; dispersing the precursor in a sodium hydroxide solution, stirring, carrying out solid-liquid separation, washing, and drying to obtain a NiCoMoMnM-LDH high-entropy material; m salt is any one of zinc salt, ferric salt and copper salt. The preparation method disclosed by the invention not only avoids phase separation and element aggregation in the forming process of the high-entropy material, but also is high in universality, and the high-entropy hydroxide can be efficiently synthesized on a large scale; and the prepared high-entropy material is high in specific capacitance and good in rate capability and cycling stability, and can be applied to a positive electrode material of a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to NiCoMoMnM-LDH high entropy materials and preparation and application thereof. Background Art

[0002] High entropy materials (hem) are single-phase solid solutions formed by five or more elements driven by configurational entropy. Due to the high tunability of their components and the synergistic effects between the components, they are widely used in aerospace, catalysis, medical treatment, environmental protection and other fields. In recent years, high entropy compounds have also shown great potential in the field of electrochemical energy storage.

[0003] However, most of the current research on high-entropy compounds focuses on high-entropy oxides. Due to their poor electrical conductivity, high-entropy oxides have relatively low specific capacitance. High-entropy hydroxides can theoretically provide more active sites due to their unique layered structure and large specific surface area, greatly improving their electrical conductivity. Therefore, in theory, using high-entropy hydroxide materials instead of high-entropy oxide materials as electrode materials for supercapacitors can effectively overcome the defect of relatively low specific capacitance of high-entropy electrode materials. However, in actual production, high-entropy hydroxides are often difficult to prepare. One reason is that most preparation methods of high-entropy compounds require synthesis at high temperatures (2000K~3000K). Due to the poor high temperature resistance of hydroxides, hydroxides are easily decomposed into oxides. Another reason is that due to the differences in the composition of high-entropy materials, it is difficult to obtain a stable structure of high-entropy hydroxides by general methods, which makes high-entropy hydroxides prone to volume expansion during charging and discharging, resulting in poor cycle stability.

[0004] In order to solve the above technical problems, the present invention provides NiCoMoMnM-LDH high entropy material and its preparation and application. Summary of the invention

[0005] In order to solve the deficiencies in the above-mentioned prior art, the present invention provides NiCoMoMnM-LDH high entropy material and its preparation and application. The present invention uses metal organic framework (MOF) material as a template, relying on the unique framework structure and easy-to-adjust components of MOF material, to synthesize NiCoMoMnM-LDH high entropy material. According to the characterization results, the effects of different components on its morphology, structure and electrochemical properties are studied. Then, the NiCoMoMnM-LDH high entropy material is subjected to density functional theory (DFT) calculation to analyze its band structure, state density and charge density.

[0006] The NiCoMoMnM-LDH high entropy material of the present invention and its preparation and application are achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a NiCoMoMnM-LDH high entropy material, comprising the following steps:

[0008] Evenly dispersing nickel salt, cobalt salt, manganese salt and M salt in an ethanol aqueous solution to obtain solution A;

[0009] Evenly dispersing molybdate and 2,5-dihydroxyterephthalic acid in an organic solvent to obtain a solution B;

[0010] After mixing the solution A and the solution B, a hydrothermal reaction is carried out at 110-130° C., solid-liquid separation is performed, and the obtained solid component is washed and dried to obtain a precursor NiCoMoMnM-MOF;

[0011] The precursor NiCoMoMnM-MOF is uniformly dispersed in a sodium hydroxide solution, stirred, and then solid-liquid separated, and the obtained solid component is washed and dried to obtain the NiCoMoMnM-LDH high entropy material;

[0012] Wherein, the M salt is any one of zinc salt, iron salt and copper salt.

[0013] Preferably, the molar ratio of the nickel salt, cobalt salt, manganese salt and M salt is 1.8-2.2:1:1:1;

[0014] The molar ratio of molybdate and 2,5-dihydroxyterephthalic acid in the solution B to the cobalt salt in the solution A is 0.14:0.5:0.9-1.1.

[0015] Preferably, the nickel salt, cobalt salt, manganese salt, and M salt are any one of chloride, nitrate, sulfate, and carbonate of the corresponding metal ions;

[0016] The molybdate is ammonium molybdate tetrahydrate or sodium molybdate.

[0017] Preferably, the concentration of ethanol in the ethanol aqueous solution is 48wt.% to 52wt.%;

[0018] The usage ratio of the cobalt salt to the ethanol aqueous solution is 0.3 mmol:4-10 mL.

[0019] Preferably, the organic solvent is N,N-dimethylformamide;

[0020] The usage ratio of the organic solvent to the molybdate is 45-55 mL:0.04 mmol.

[0021] Preferably, the concentration of the sodium hydroxide solution is 0.75 to 1.5 mol / L;

[0022] The usage ratio of the precursor NiCoMoMnM-MOF to the sodium hydroxide solution is 0.1 g:9-11 mL.

[0023] Preferably, the reaction time of the hydrothermal reaction is 16 to 32 hours.

[0024] Preferably, the stirring rate of the stirring treatment is 400-600 r / min, and the stirring time is 4-8 h.

[0025] The second object of the present invention is to provide a NiCoMoMnM-LDH high entropy material prepared by the above preparation method.

[0026] The third object of the present invention is to provide an application of the above-mentioned NiCoMoMnM-LDH high entropy material in a supercapacitor positive electrode material.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] Based on the shortcomings of traditional high-entropy hydroxides, such as harsh preparation conditions, poor high temperature resistance and easy decomposition, the method of the invention uses metal organic framework (MOF) materials as templates and relies on the unique framework structure and easy-to-adjust components of MOF materials to synthesize NiCoMoMnM-LDH high-entropy materials. The band structure, state density and charge density are analyzed by density functional theory (DFT) calculation, further revealing the electrochemical enhancement mechanism of high-entropy LDH.

[0029] The template re-etching method selected by the present invention not only successfully avoids phase separation and element aggregation in the process of high entropy material formation, but also has certain universality, which is conducive to the efficient and large-scale synthesis of high entropy hydroxides. The selected 2,5-dihydroxyterephthalic acid has selective specificity for various metals in the present invention, can form coordination compounds with various metals, and can easily form NiCoMoMnM-MOF under hydrothermal conditions. In addition, 2,5-dihydroxyterephthalic acid contains -OH groups, so the synthesized NiCoMoMnM-MOF has -OH groups, which match the -OH in the sodium hydroxide solution involved in the subsequent etching, providing more reactive sites for etching, and more easily forming lamellar LDH. At the same time, after the addition of Co, Mo, Mn, and M elements, a synergistic effect is generated between the five metal elements, a large number of impurity energy levels are introduced between the valence band and the conduction band, the band gap is reduced, and electrons are more easily transferred to the conduction band, which increases the conductivity of the material. In addition, two other high-entropy-LDH materials were successfully prepared in the same way by adjusting the components, indicating that this method can effectively adjust the morphology, pore structure, specific surface area and other properties of the material, and thus can better adapt to the production needs in multiple fields and scenarios. The prepared NiCoMoMnM-LDH composite material has high specific capacitance, good rate performance and cycle stability, and is widely used in supercapacitor positive electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD diagram of the precursor NiCoMoMnZn-MOF material prepared in Example 1-3;

[0031] Figure 2 XRD pattern of NiCoMoMnM-LDH high entropy material prepared in Example 1-3;

[0032] Figure 3 This is a SEM image of the NiCoMoMnZn-LDH high entropy material prepared in Example 1;

[0033] Figure 4 TEM image of the NiCoMoMnZn-LDH high entropy material prepared in Example 1;

[0034] Figure 5 for Figure 4 High-resolution transmission electron microscopy image of the boxed area;

[0035] Figure 6 for Figure 4 Selected area electron diffraction pattern of the boxed area;

[0036] Figure 7 The EDS analysis results of the NiCoMoMnZn-LDH high entropy material prepared in Example 1;

[0037] Figure 8 Element distribution diagram of NiCoMoMnZn-LDH high entropy material prepared in the selected single Example 1;

[0038] Fig. 9 The constant current charge-discharge curve of the NiCoMoMnZn-LDH high entropy material prepared in Example 1-3 at a current density of 0.5 A / g;

[0039] Fig.10 The constant current charge and discharge diagram of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 at different current densities;

[0040] Fig.11 This is a cycle performance diagram of the NiCoMoMnZn-LDH high entropy material prepared in Example 1;

[0041] Fig.12 The energy band structure and state density diagram of Ni(OH)2 obtained based on density functional theory;

[0042] Fig.13 The energy band structure and state density diagram of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 obtained based on density functional theory. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0044] The present invention provides a NiCoMoMnM-LDH high entropy material, and the preparation method thereof is as follows:

[0045] Evenly dispersing nickel salt, cobalt salt, manganese salt and M salt in an ethanol aqueous solution to obtain solution A;

[0046] Evenly dispersing molybdate and 2,5-dihydroxyterephthalic acid in an organic solvent to obtain a solution B;

[0047] After mixing the solution A and the solution B, a hydrothermal reaction is carried out at 110-130° C., solid-liquid separation is performed, and the obtained solid component is washed and dried to obtain a precursor NiCoMoMnM-MOF;

[0048] The precursor NiCoMoMnM-MOF is uniformly dispersed in a sodium hydroxide solution, stirred, and then solid-liquid separated, and the obtained solid component is washed and dried to obtain the NiCoMoMnM-LDH high entropy material;

[0049] Wherein, the M salt is any one of zinc salt, iron salt and copper salt.

[0050] It should be noted that the present invention improves the crystallinity of the precursor NiCoMoMnM-MOF obtained by the hydrothermal reaction by regulating the reaction temperature of the hydrothermal reaction to 110-130°C and the reaction time to 16-32h, so that the composite material formed subsequently can maintain the structure of the MOF material, thereby improving the uniform and good electrochemical stability of the composite material when used as a supercapacitor positive electrode material. When preparing the precursor NiCoMoMnM-MOF, nickel salt, cobalt salt, manganese salt, and M salt are respectively made into solution A, and molybdate and 2,5-dihydroxyterephthalic acid are made into solution B, and then solution A and solution B are mixed and hydrothermally reacted to obtain the precursor NiCoMoMnM-MOF. Among them, ethanol aqueous solution is used as a solvent to form a uniform solution A with nickel salt, cobalt salt, manganese salt, and M salt, and in a preferred embodiment of the present invention, the concentration of ethanol in the ethanol aqueous solution is 48wt.% to 52wt.%; the amount ratio of the cobalt salt to the ethanol aqueous solution is 0.3mmol:4-10mL. In order to make the organic ligand fully soluble in the organic solvent and have good thermal stability, in a preferred embodiment of the present invention, N,N-dimethylformamide (DMF) is used as the organic solvent to form a solution B with uniform components with molybdate and 2,5-dihydroxyterephthalic acid, and in a preferred embodiment of the present invention, the usage ratio of the organic solvent to the molybdate is 45-55mL:0.04mmol.

[0051] The present invention does not limit the specific forms of nickel salts, cobalt salts, manganese salts, and M salts, and can be selected from any of the corresponding chlorides, nitrates, sulfates, and carbonates. However, considering the cost and safety issues, the present invention preferably uses chlorides to prepare NiCoMoMnM-LDH high entropy materials. In order to ensure that high entropy materials can be obtained, the molar ratio of the added nickel salts, cobalt salts, manganese salts, and M salts is controlled within the range of 1.8 to 2.2:1:1:1, so that the material presents a disordered structure through the entropy increase effect of doping with approximately equal molar ratios; at the same time, when solution A is mixed with solution B, the molar ratio of molybdate, 2,5-dihydroxyterephthalic acid in solution B to the cobalt salt in the solution A is 0.14:0.5:0.9 to 1.1. Among them, in the present invention, molybdate can be selected from any one of tetrahydrated ammonium molybdate and sodium molybdate.

[0052] In the present invention, when nickel salt, cobalt salt, manganese salt and M salt are dispersed in ethanol aqueous solution, stirring or ultrasonic method can be used for dispersion, as long as they are uniformly dispersed. In order to make nickel salt, cobalt salt, manganese salt and M salt fully and uniformly dispersed in ethanol aqueous solution, in a preferred embodiment of the present invention, ultrasonic combined with stirring method is used for dispersion, and firstly ultrasonically for 4 to 6 minutes under the condition of ultrasonic frequency of 40KHz, and then stirred at a stirring rate of 400 to 600r / min for 20 to 40 minutes, so as to obtain solution A.

[0053] In the present invention, when dispersing molybdate and 2,5-dihydroxyterephthalic acid in an organic solvent, stirring or ultrasonic dispersion can be used as long as they are uniformly dispersed. In order to make molybdate and 2,5-dihydroxyterephthalic acid uniformly dispersed in an organic solvent, in a preferred embodiment of the present invention, stirring is used for dispersion, and the stirring rate is 400-600 r / min, and the stirring time is 20-40 min.

[0054] In the present invention, when mixing solution A and solution B, stirring or ultrasonic dispersion can be used as long as they are uniformly dispersed. In order to facilitate the thorough mixing of solution A and solution B, in a preferred embodiment of the present invention, stirring is used for dispersion, and the stirring rate is 400-600 r / min, and the stirring time is 20-40 min.

[0055] In the present invention, a mixed solution of solution A and solution B is subjected to a hydrothermal reaction. In order to allow each component to fully react and contact to obtain a high entropy material, the temperature of the hydrothermal reaction is 110 to 130° C. and the reaction time is 16 to 32 hours. In order to obtain a pure precursor NiCoMoMnM-MOF, the product of the hydrothermal reaction is first subjected to solid-liquid separation. In order to improve the solid-liquid separation efficiency, in a preferred embodiment of the present invention, solid-liquid separation is performed by centrifugation, and the centrifugal rate is 4000 to 8000 r / min, and the centrifugal time is 5 minutes. When washing the solid product obtained by solid-liquid separation, in a preferred embodiment of the present invention, N, N-dimethylformamide, deionized water and anhydrous ethanol are used to wash 2 to 3 times respectively. When drying the product obtained by washing, a vacuum drying oven is used for drying, and the drying temperature is 60 to 80° C. and the drying time is 12 to 24 hours.

[0056] The present invention uses sodium hydroxide solution as an etching solution, disperses the precursor NiCoMoMnM-MOF in the sodium hydroxide solution, and forms a lamellar LDH by etching, thereby obtaining the NiCoMoMnM-LDH composite material of the present invention. Among them, in order to ensure that the material obtained after etching can still maintain the morphology of the precursor NiCoMoMnM-MOF, in a preferred embodiment of the present invention, a sodium hydroxide solution with a concentration of 0.75 to 1.5 mol / L is used as an etching solution, and the amount ratio of the above-mentioned precursor NiCoMoMnM-MOF to the sodium hydroxide solution is 0.1g:9 to 11mL. The present invention preferably uses a stirring method to disperse the precursor NiCoMoMnM-MOF in a sodium hydroxide solution, and the stirring rate is 400 to 600 r / min, and the stirring time is 4 to 8h.

[0057] Example 1

[0058] This embodiment provides a NiCoMoMnZn-LDH high entropy material, and its preparation method is as follows:

[0059] Step 1, prepare solution A and solution B:

[0060] 1) 3 mL of deionized water and 3 mL of anhydrous ethanol were mixed by magnetic stirring to obtain an ethanol aqueous solution, and then 0.6 mmol of nickel chloride hexahydrate, 0.3 mmol of cobalt chloride hexahydrate, 0.3 mmol of manganese chloride hexahydrate, and 0.3 mmol of zinc chloride hexahydrate were dissolved in the above-prepared ethanol aqueous solution, and ultrasonicated for 5 min, and then stirred at a stirring speed of 400 r / min for 30 min to obtain solution A;

[0061] 2) 0.04 mmol of tetrahydrated ammonium molybdate and 0.15 mmol of 2,5-dihydroxyterephthalic acid were placed in 50 mL of DMF and stirred at a stirring speed of 400 r / min for 30 min to obtain a solution B.

[0062] Step 2, preparation of precursor NiCoMoMnZn-MOF:

[0063] Solution A and solution B were mixed, stirred at a stirring speed of 400 r / min for 30 minutes, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed in a blast drying oven for hydrothermal reaction at a temperature of 120°C for 24 hours, naturally cooled to room temperature, and then centrifuged at a centrifugal speed of 8000 r / min for 5 minutes. The solid obtained by centrifugation was washed with N,N-dimethylformamide, deionized water and anhydrous ethanol for 3 times respectively, and then dried in a vacuum drying oven at a drying temperature of 60°C and a drying time of 24 hours. After drying, a brown-yellow powder was obtained, which was the precursor NiCoMoMnZn-MOF.

[0064] Step 3, remove MOF by etching to obtain NiCoMoMnZn-LDH high entropy material:

[0065] 0.5 g of the precursor NiCoMoMnZn-MOF prepared in step 2 was placed in 50 mL of a sodium hydroxide solution with a molar concentration of 1.5 mol / L, and stirred at a stirring speed of 400 r / min for 8 h; then centrifuged at a centrifugal speed of 8000 r / min for 5 min, and the solid obtained by centrifugation was subsequently centrifuged to separate the solid, and the solid was washed with deionized water and anhydrous ethanol for 3 times, respectively, and then dried in a vacuum drying oven at 60°C for 24 h to obtain a dark green powder, which is the NiCoMoMnZn-LDH high entropy material.

[0066] Example 2

[0067] This embodiment provides a NiCoMoMnCu-LDH high entropy material, and its preparation method is as follows:

[0068] Step 1, prepare solution A and solution B:

[0069] 1) 3 mL of deionized water and 3 mL of anhydrous ethanol were mixed by magnetic stirring to obtain an ethanol aqueous solution, and then 0.6 mmol of nickel chloride hexahydrate, 0.3 mmol of cobalt chloride hexahydrate, 0.3 mmol of manganese chloride hexahydrate, and 0.3 mmol of cupric chloride hexahydrate were dissolved in the above-prepared ethanol aqueous solution, ultrasonicated for 5 min, and then stirred at a stirring speed of 400 r / min for 30 min to obtain solution A;

[0070] 2) 0.04 mmol of tetrahydrated ammonium molybdate and 0.15 mmol of 2,5-dihydroxyterephthalic acid were placed in 50 mL of DMF and stirred at a stirring speed of 400 r / min for 30 min to obtain a solution B.

[0071] Step 2, preparation of precursor NiCoMoMnCu-MOF:

[0072] Solution A and solution B were mixed, stirred at a stirring speed of 400 r / min for 30 minutes, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed in a blast drying oven for hydrothermal reaction at a temperature of 120°C for 24 hours, naturally cooled to room temperature, and then centrifuged at a centrifugal speed of 8000 r / min for 5 minutes. The solid obtained by centrifugation was washed with N,N-dimethylformamide, deionized water and anhydrous ethanol for 3 times respectively, and then dried in a vacuum drying oven at a drying temperature of 60°C and a drying time of 24 hours. After drying, a brown-yellow powder was obtained, which was the precursor NiCoMoMnCu-MOF.

[0073] Step 3, remove MOF by etching to obtain NiCoMoMnCu-LDH high entropy material:

[0074] 0.5 g of the precursor NiCoMoMnCu-MOF prepared in step 2 was placed in 50 mL of a sodium hydroxide solution with a molar concentration of 1.5 mol / L, and stirred at a stirring speed of 400 r / min for 8 h; then centrifuged at a centrifugal speed of 8000 r / min for 5 min, and the solid obtained by centrifugation was subsequently centrifuged to separate the solid, and the solid was washed 3 times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at a temperature of 60°C for 24 h to obtain a dark green powder, which is the NiCoMoMnCu-LDH high entropy material.

[0075] Example 3

[0076] This embodiment provides a NiCoMoMnFe-LDH high entropy material, and its preparation method is as follows:

[0077] Step 1, prepare solution A and solution B:

[0078] 1) 3 mL of deionized water and 3 mL of anhydrous ethanol were mixed by magnetic stirring to obtain an ethanol aqueous solution, and then 0.6 mmol of nickel chloride hexahydrate, 0.3 mmol of cobalt chloride hexahydrate, 0.3 mmol of manganese chloride hexahydrate, and 0.3 mmol of ferric chloride hexahydrate were dissolved in the ethanol aqueous solution prepared above, and ultrasonicated for 5 min, and then stirred at a stirring speed of 400 r / min for 30 min to obtain solution A;

[0079] 2) 0.04 mmol of tetrahydrated ammonium molybdate and 0.15 mmol of 2,5-dihydroxyterephthalic acid were placed in 50 mL of DMF and stirred at a stirring speed of 400 r / min for 30 min to obtain a solution B.

[0080] Step 2, preparation of precursor NiCoMoMnFe-MOF:

[0081] Solution A and solution B were mixed, stirred at a stirring speed of 400 r / min for 30 min, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed in a blast drying oven for hydrothermal reaction at a temperature of 120°C for 24 h, naturally cooled to room temperature, and then centrifuged at a centrifugal speed of 8000 r / min for 5 min. The solid obtained by centrifugation was washed with N,N-dimethylformamide, deionized water and anhydrous ethanol for 3 times respectively, and then dried in a vacuum drying oven at a drying temperature of 60°C and a drying time of 24 h. After drying, a brown-yellow powder was obtained, which was the precursor NiCoMoMnFe-MOF.

[0082] Step 3, etching to remove MOF, and obtaining NiCoMoMnFe-LDH high entropy material:

[0083] 0.5 g of the precursor NiCoMoMnFe-MOF prepared in step 2 was placed in 50 mL of a sodium hydroxide solution with a molar concentration of 1.5 mol / L, and stirred at a stirring speed of 400 r / min for 8 h; then centrifuged at a centrifugal speed of 8000 r / min for 5 min, and the solid obtained by centrifugation was subsequently centrifuged to separate the solid, and the solid was washed 3 times with deionized water and anhydrous ethanol respectively, and then dried in a vacuum drying oven at a temperature of 60°C for 24 h to obtain a dark green powder, which is the NiCoMoMnFe-LDH high entropy material.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is only that:

[0086] In this comparative example, ultrasonic compounding is used instead of the hydrothermal compounding in Example 1;

[0087] In this comparative example, the ultrasonic compounding is performed so that the ultrasonic frequency is 40 KHz and the ultrasonic time is 2 hours.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is only that:

[0090] In this comparative example, solution A and solution B are not prepared separately, and each raw material is directly dissolved and mixed with a mixed solvent of ethanol aqueous solution and DMF, and then the treatment of step 2 is performed, that is:

[0091] 3 mL of deionized water, 3 mL of anhydrous ethanol and 50 mL of DMF were mixed using magnetic stirring to obtain a mixed solvent; 0.6 mmol of nickel chloride hexahydrate, 0.3 mmol of cobalt chloride hexahydrate, 0.3 mmol of manganese chloride hexahydrate, 0.3 mmol of zinc chloride hexahydrate, 0.04 mmol of ammonium molybdate tetrahydrate and 0.15 mmol of 2,5-dihydroxyterephthalic acid were added, ultrasonicated for 5 min, and then stirred at a stirring speed of 400 r / min for 30 min.

[0092] Experimental Section

[0093] (I) XRD test

[0094] The present invention takes the precursor NiCoMoMnM-MOF prepared in Examples 1-3 and the NiCoMoMnM-LDH high entropy material prepared in Examples 1-3 as examples, and performs XRD tests on them respectively. The test results are as follows: Figure 1 and Figure 2shown.

[0095] in, Figure 1 XRD pattern of the precursor NiCoMoMnM-MOF prepared in Example 1-3; Figure 2 This is the XRD pattern of the NiCoMoMnM-LDH high entropy material prepared in Examples 1-3.

[0096] And by Figure 1 It can be seen that the diffraction peaks of the MOF material prepared by the precursor NiCoMoMnM-MOF prepared in Examples 1-3 are basically consistent with the Ni-MOF74 standard card, indicating that the MOF material has been successfully synthesized.

[0097] And by Figure 2 It can be seen that the NiCoMoMnM-LDH high entropy materials prepared in Examples 1-3 can observe derivative peaks belonging to LDH at 2θ=11.6°, 21.2°, 34.5°, 45.7°, and 60.5°, indicating the successful synthesis of the LDH material.

[0098] (ii) SEM test

[0099] The present invention takes the NiCoMoMnZn-LDH high entropy material prepared in Example 1 as an example, and performs SEM test on it. The test results are as follows: Figure 3 shown.

[0100] And by Figure 3 It can be seen that in the SEM image of the NiCoMoMnZn-LDH high entropy material prepared in Example 1, the NiCoMoMnZn-LDH high entropy material as a whole presents a nanoflower morphology formed by the accumulation of curved sheets, with a diameter of about 2 μm. The curved sheet structure increases the contact area between the active substance and the electrolyte solution, and promotes the electron transfer between the electrode and the electrolyte. At the same time, the unique layered structure can effectively avoid the self-aggregation phenomenon between the active substances during the charge and discharge process, and can effectively improve the cycle stability of the electrode material.

[0101] (III) TEM test

[0102] The present invention takes the NiCoMoMnZn-LDH high entropy material prepared in Example 1 as an example and performs TEM test on it. The test results are as follows: Figure 4 As shown. And by Figure 4 It can be observed more clearly that in the TEM of the NiCoMoMnZn-LDH high entropy material prepared in Example 1, NiCoMoMnZn-LDH is a nanosphere structure formed by stacking of sheets, and the sheets constituting the nanosphere are relatively thin.

[0103] The present invention also Figure 4The part in the box area was tested by high-resolution transmission electron microscopy (HRTEM), and the test results are as follows Figure 5 As shown, it can be seen that the lattice fringes with lattice spacings of 0.245 nm, 0.205 nm and 0.152 nm in the NiCoMoMnZn-LDH high entropy material prepared in Example 1 correspond to the (0 1 2), (1 0 7) and (1 1 0) crystal planes of NiCoMoMnZn-LDH, respectively, indicating the successful synthesis of layered NiCoMoMnZn-LDH.

[0104] The present invention also Figure 4 The selected area electron diffraction (SAED) test was performed on the part in the box area, and the test results are as follows Figure 6 As shown, it can be seen that the SAED pattern of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 shows diffraction rings with a diffuse structure rather than a lattice, indicating that the NiCoMoMnZn-LDH high entropy material prepared in Example 1 has poor crystallinity, which may be due to the increase in the disorder of the crystal caused by the high entropy effect, thereby reducing the crystallinity of the structure.

[0105] (IV) EDS analysis

[0106] In order to determine the atomic ratio and element distribution of each component in the NiCoMoMnZn-LDH high entropy material, the present invention also performed EDS analysis and element distribution analysis on the NiCoMoMnZn-LDH high entropy material prepared in Example 1, and the results are as follows: Figure 7 and Figure 8 shown.

[0107] Figure 7 From the EDS analysis results of the NiCoMoMnZn-LDH high entropy material prepared in Example 1, it can be seen that the ratio of the five metals Ni, Co, Mo, Mn and Zn is close to 2:1:1:1:1, which is close to the experimental addition value.

[0108] Figure 8 This is the element distribution diagram of the NiCoMoMnZn-LDH high entropy material prepared in the selected single Example 1. It can be seen that the five elements Ni, Co, Mo, Mn and Zn are distributed on the nanospheres in a relatively uniform manner.

[0109] (V) Electrochemical performance test

[0110] 1) Specific capacitance at a current density of 0.5 A / g

[0111] The present invention uses Ni(OH)2 and NiCoMnZn-LDH prepared in comparative examples 1-2 as a control group, and the NiCoMoMnM-LDH high entropy material prepared in examples 1-3 as an experimental group, and tests their constant current charge and discharge performance at a current density of 0.5 A / g.

[0112] According to the test results, the specific capacitance of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 can reach up to 1810.2F / g, the specific capacitance of the high entropy NiCoMoMnCu-LDH high entropy material prepared in Example 2 is 1450.1F / g, the specific capacitance of the high entropy NiCoMoMnFe-LDH high entropy material prepared in Example 3 is 814.5F / g, and the specific capacitance of the NiCoMnZn-LDH prepared in Comparative Example 1 is 872.3F·g -1 The specific capacitance of NiCoMnZn-LDH prepared in Comparative Example 2 is 1436.2 F·g -1 By comparing the specific capacitance of Example 1 with Comparative Examples 1 and 2, it can be seen that the hydrothermal method of compounding and the method of mixing the raw materials after forming solutions separately in the present invention have an important influence on the electrochemical properties of the constructed NiCoMoMnM-LDH high entropy material, indicating that the excellent electrochemical performance of the NiCoMoMnM-LDH high entropy material prepared by the present invention is not improved by a single factor, but is achieved through the organic combination of multiple factors.

[0113] The present invention summarizes the constant current charge-discharge curves of Ni(OH)2 and the NiCoMoMnM-LDH high entropy materials prepared in Examples 1-3 at a current density of 0.5A / g as follows: Fig. 9 As shown, it can be seen that the specific capacitance of the NiCoMoMnM-LDH high entropy material prepared in Examples 1-3 of the present invention is greatly improved compared with the single Ni(OH)2 material, and the NiCoMoMnZn-LDH high entropy material has the highest specific capacitance, indicating that the doped metal elements have an important influence on the electrochemical properties of the NiCoMoMnM-LDH high entropy material. Therefore, in the present invention, the M salt used is preferably selected from any one of zinc salts and copper salts, more preferably zinc salt.

[0114] 2) Specific capacitance at different current densities

[0115] The present invention takes the NiCoMoMnZn-LDH high entropy material prepared in Example 1 as an example, and tests its constant current charge and discharge performance at different current densities (0.5, 1, 2, 5, 10, 20 A / g), and the test results are as follows: Fig.10 shown.

[0116] Fig.10The constant current charge and discharge diagrams of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 at different current densities show that the specific capacitance of the high entropy electrode material decreases with the increase of current density. This is because at high current density, the transmission speed of electrons is greater than the transmission speed of ions, resulting in a large amount of ion accumulation at the electrolyte / electrode interface and concentration polarization. At high current density, the attenuation degree of the specific capacitance of the electrode material is also an important indicator for evaluating the performance of the supercapacitor.

[0117] Calculation shows that the specific capacitance of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 at different current densities of 0.5, 1, 2, 5, 10, and 20 A / g are 1810.2 F / g, 1593.7 F / g, 1086.6 F / g, 824.0 F / g, 742.5 F / g, and 653.0 F / gF / g, respectively, indicating that the composite material has a higher specific capacitance, and the specific capacitance at a current density of 20 A / g can still maintain 36.1% of the specific capacitance at a current density of 0.5 A / g, which also indicates that the material has good rate performance.

[0118] 3) Cycle performance

[0119] The present invention takes the NiCoMoMnZn-LDH high entropy material prepared in Example 1 as an example, and tests the specific capacitance after 3000 cycles. Fig.11 shown.

[0120] And by Fig.11 It can be seen that the specific capacitance of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 can still maintain 89.2% of the initial capacitance after 3000 cycles, indicating that the material has good cycle stability.

[0121] (VI) Density functional theory calculations

[0122] The present invention uses the Cambridge Sequential Total Energy Package (CASTEP) code to perform DFT calculations based on first principles. The GGA-PBE functional is used as the electron exchange correlation function. A Ni(OH)2 layer with two layers, each containing 12 metal atoms, 24 H atoms and 24 O atoms, is used. As the initial model (i.e. Ni(OH)2 calculation model), the LDH calculation model consisting of Co, Mo, Mn, and Zn replacing one Ni atom in each layer was tested for energy convergence based on the cutoff energy and k-point. The final cutoff energy was 500eV; the k-point was 3x3x3. The energy convergence criterion is less than 10-5eV, and the maximum force on the atom is less than Atomic stress deviation is less than 0.05GPa and maximum displacement is less than In order to eliminate the interaction between supercells, the present invention establishes a The vacuum layer, the calculation results are as follows Fig.12 and Fig.13 shown.

[0123] in, Fig.12 The energy band structure and state density diagram of Ni(OH)2 obtained based on density functional theory; Fig.13 The energy band structure and state density diagram of the NiCoMoMnZn-LDH high entropy material prepared in Example 1 obtained based on density functional theory.

[0124] By comparison Fig.12 and Fig.13 It can be observed that there is an obvious band gap between the valence band and the conduction band of the two materials, and no band passes through the Fermi level. Therefore, it can be judged that the NiCoMoMnM-LDH composite material prepared by the present invention is a material with semiconductor properties. After Co, Mo, Mn and Zn are doped, a large number of impurity energy levels are introduced into the conduction band and the valence band due to the induction of the 3d and 4d orbitals of the metal. The top of the valence band and the bottom of the conduction band are close to the Fermi level, and the band gap width is reduced from 1.63eV to 0.27eV, which increases the probability of electrons reaching the conduction band, thereby improving the conductivity of the electrode material.

[0125] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing NiCoMoMnM-LDH high entropy material, characterized in that: The following steps are involved: Evenly dispersing nickel salt, cobalt salt, manganese salt and M salt in an ethanol aqueous solution to obtain solution A; Evenly dispersing molybdate and 2,5-dihydroxyterephthalic acid in an organic solvent to obtain a solution B; After mixing the solution A and the solution B, a hydrothermal reaction is carried out at 110-130° C., solid-liquid separation is performed, and the obtained solid component is washed and dried to obtain a precursor NiCoMoMnM-MOF; The precursor NiCoMoMnM-MOF is uniformly dispersed in a sodium hydroxide solution, stirred, and then solid-liquid separated, and the obtained solid component is washed and dried to obtain the NiCoMoMnM-LDH high entropy material; Wherein, the M salt is any one of zinc salt, iron salt and copper salt.

2. The preparation method according to claim 1, characterized in that The molar ratio of the nickel salt, cobalt salt, manganese salt and M salt is 1.8-2.2:1:1:1; The molar ratio of molybdate and 2,5-dihydroxyterephthalic acid in the solution B to the cobalt salt in the solution A is 0.14:0.5:0.9-1.

1.

3. The preparation method according to claim 1, characterized in that: The nickel salt, cobalt salt, manganese salt, and M salt are any one of chloride, nitrate, sulfate, and carbonate of the corresponding metal ions; The molybdate is ammonium molybdate tetrahydrate or sodium molybdate.

4. The preparation method according to claim 1, characterized in that: The concentration of ethanol in the ethanol aqueous solution is 48wt.% to 52wt.%; The usage ratio of the cobalt salt to the ethanol aqueous solution is 0.3 mmol:4-10 mL.

5. The preparation method according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide; The usage ratio of the organic solvent to the molybdate is 45-55 mL:0.04 mmol.

6. The preparation method according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.75-1.5 mol / L; The usage ratio of the precursor NiCoMoMnM-MOF to the sodium hydroxide solution is 0.1 g:9-11 mL.

7. The preparation method according to claim 1, characterized in that: The reaction time of the hydrothermal reaction is 16 to 32 hours.

8. The preparation method according to claim 1, characterized in that: The stirring rate of the stirring treatment is 400-600 r / min, and the stirring time is 4-8 hours.

9. A NiCoMoMnM-LDH high entropy material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the NiCoMoMnM-LDH high entropy material according to claim 9 in a supercapacitor positive electrode material.

Citation Information

Cited By

  • Flower-like FeCoNiMnPt high-entropy magnetic alloy powder and preparation method thereof

    CN119794366A

  • Graphite felt / high-entropy MOF electrode, lignin-based fuel cell and method for co-production of aviation fuel components

    CN120376664A

  • A method for co-producing aviation fuel components using a graphite felt / high-entropy MOF electrode, a lignin-based fuel cell, and a method for the production of aviation fuel components.

    CN120376664B